2008
DOI: 10.1002/rra.1209
|View full text |Cite
|
Sign up to set email alerts
|

Environmental flow enhances native fish spawning and recruitment in the Murray River, Australia

Abstract: Environmental flows aim to mimic components of a river's natural flow variability, including the magnitude, frequency, timing, duration, rate of change and the predictability of flow events. Aspects of the natural flow regime are thought to be linked to critical components of the life history strategies of many riverine fishes, including spawning and recruitment. In the Murray River, Australia, environmental flows are increasingly being used as a restoration tool; however, there is little information about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
155
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(164 citation statements)
references
References 32 publications
7
155
1
1
Order By: Relevance
“…correct species identification), habitat rehabilitation, environmental flows and fishways have either not been monitored or their benefits to trout cod are difficult to quantify (e.g. King et al 2009). Many other actions have been successful, and, in addition, there is a range of broader fish-related management actions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…correct species identification), habitat rehabilitation, environmental flows and fishways have either not been monitored or their benefits to trout cod are difficult to quantify (e.g. King et al 2009). Many other actions have been successful, and, in addition, there is a range of broader fish-related management actions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Os biólogos da década de 1970 e 1980 acreditavam que vazões elevadas em períodos de secas garantiriam melhor qualidade de vida aos peixes. Entretanto, na visão atual, observa-se que os modelos que se aproximam do regime de fluxo natural de um rio, garantem melhor qualidade de vida para flora e fauna aquáticas (Chang et al, 2008, Sanderson et al, 2008Deitch et al, 2009a), pois vazões altas podem beneficiar determinada espécie, mas comprometer outras e vice-versa (King et al, 2008).…”
Section: A Vazão Ecológicaunclassified
“…Subsequent larval survival and recruitment success is thought to be linked to the occurrence of overbank flooding, although there remains uncertainty surrounding the influence of flows on the distribution and abundance of Murray cod (Rowland, 1989;Koehn and Harrington, 2006;King et al, 2009). Although thermal impacts (cold-water pollution) are known to influence egg and larval survival (Todd et al, 2005), the species has been demonstrated to spawn annually in both regulated and unregulated systems (Humphries, 2005;Koehn and Harrington, 2006;King et al, 2009). The larval duration of the Murray cod is typically o1 month, and sexual maturity is reach at ∼ 4-6 years of age (Rowland, 2004).…”
Section: Introductionmentioning
confidence: 99%